More than meets the dimer: What is the quaternary structure of the glucocorticoid receptor? - Presman, Diego Martin (2017)
It is widely accepted that the glucocorticoid receptor (GR), a ligand-regulated transcription factor that triggers anti-inflammatory responses, binds specific response elements as a homodimer. Here, we will discuss the original primary data that established this model and contrast it with a recent report characterizing the GR–DNA complex as a tetramer.